Effects and Mechanisms of Lauric Acid on the Quality of Fresh White Salted Noodles - Jing SUN; Fangyi ZHAO; Mengyao LÜ; Qianqian CHEN; Xiao WAN; Jing DU; Xuedong WANG (Shipin gongye ke-ji)
To explore the effect of lauric acid (LA) on the quality of fresh wet noodles with different salts and its underlying mechanism, this study investigated the effect of LA on the cooking quality and sensory quality of fresh wet noodles with 1% sodium chloride (NaCl) and 0.4% sodium tripolyphosphate (STPP), and revealed the mechanism of lauric acid regulation on fresh wet noodles with different salts from the perspective of wheat starch characteristics and structural changes. The results showed that LA reduced the cooking loss and water absorption of fresh wet noodles without salt were reduced by 8.9% and 15.72%, respectively. LA significantly (P<0.05) improved the quality of fresh wet noodles with salts, especially fresh wet noodles with STPP, the water absorption, cooking loss, solubility and swelling potential of fresh wet noodles with LA were reduced by 9.53%, 12.78%, 37.92% and 45.00%, respectively, and the resistant starch (RS) content was increased by 35.72% due to LA incorporation. Electronic tongue analysis showed that the addition of LA had little effect on the flavor of fresh wet noodles with salts. The addition of LA significantly (P<0.05) increased the order degree and crystallinity of starch in raw wet white salted noodles, and characteristic peaks of complexes appeared. In summary, LA could form starch-lipid or starch-lipid-protein complexes with wheat starch and protein, thereby improving the quality of fresh wet noodles with salt.